Abuse Liability of Cigarettes and Little Cigars in Adult Smokers - Cunningham, Colin S.; Miller, Mollie E.; Pickworth, Wallace B.; Salazar, Esther; Reissig, Chad J. (Tobacco regulatory science, 2019)
Objectives: Little cigars resemble cigarettes but are not subject to the US Food and Drug Administration's flavor restrictions on cigarettes. This within-subject laboratory study assessed the abuse liability of cigarettes and little cigars of varying flavors. Methods: Forty-eight adult cigarette smokers who also smoke little cigars or cigarillos completed 4 sessions that differed by tobacco product smoked: usual brand cigarette, unflavored, cherry, and menthol little cigars. Expired breath CO (COex), plasma nicotine, physiological measures, smoking topography, and subjective measures were assessed during and after each session. Results: Compared to usual brand cigarettes, little cigars were associated with smaller reductions in craving and lower subjective appeal. Minor changes in COex were observed despite less tobacco smoked in some of the little cigar sessions. Cherry flavored little cigars had the highest COex boost and subjective appeal relative to unflavored and menthol flavored little cigars. Conclusions: Generally, little cigars were rated as less appealing than cigarettes. However, cherry flavored little cigars had higher subjective appeal and produced a different smoking topography compared to the unflavored and menthol flavored little cigars. These data suggest some tobacco flavors may lead to an increased abuse liability and toxicant exposure relative to others.